Comparison of Surgical Outcomes between Patients Treated with The Harmonic Scalpel and Ligasure Device During Total/ Near Total Open Thyroidectomy - Aseel Mahmood Jawad (Indian Journal of Forensic Medicine & Toxicology, 2020)
Over the last few years many surgeons have begun to utilize the LigaSure device or Harmonic scalpel to perform thyroid surgery. Several papers have demonstrated the benefits of these devices over traditional hand-tying techniques. The purpose of this study was to examine our institution’s experience with the LigaSure device and Harmonic scalpel during thyroid surgery and to compare mean operative times and complications associated with each device.The aim of the study was to compare surgical time,postoperative complications and other parameters between ligasure device and harmonic scalpel in the open thyroidectomy procedure. We choose to examine our institution’s experience with the LigaSure and Harmonic scalpel during total/near total thyroidectomy